Pelatihan Literasi Digital Lembaga Untuk Lanjut Usia Indonesia (LLI) Kota Bandung - Roni Mulyana; Hendri Pramadya; Nadia Rizky Vindiazhari (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of information and communication technology has caused the trend of internet use in Indonesia to experience a significant increase. However, the increase in internet use is not accompanied by control over the negative impacts it causes, such as an increase in digital fraud, and the inability to differentiate between information and fake news (Hoax). Hoax is information created by an individual or someone containing false information or the truth cannot be checked. Hoaxes have an impact that can be detrimental to individuals and society. The elderly are one of the parties who are vulnerable to Hoaxes related to health information or digital fraud. Therefore, digital literacy training is needed. Therefore, ASMTB and Mafindo Bandung collaborates with Lembaga Lanjut Usia Indonesia (LLI) (the Bandung City Elderly Institute to organize) digital literacy learning for the elderly. Based on the results of PKM (University Community Service)observations, digital literacy training activities for the elderly are considered very useful for increasing knowledge, digital security awareness, and digital literacy skills for Bandung City LLI (Lembaga Lanjut Usia) members.